Effectiveness of Benralizumab in Improving the Quality of Life of Severe Eosinophilic Asthmatic Patients: Our Real-Life Experience - Giulia Scioscia; Giulia Scioscia; Giovanna Elisiana Carpagnano; Carla Maria Irene Quarato; Carla Maria Irene Quarato; Donato Lacedonia; Donato Lacedonia; Sonia Santamaria; Sonia Santamaria; Piera Soccio; Annarita Depalo; Paolo Fuso; et al. (Frontiers Media S.A., 2021)
Background: Severe eosinophilic asthma decreases lung function and causes worsen symptoms, often forcing recurrent maintenance corticosteroid use. The aim of our real-life study was to evaluate the effectiveness of an add-on treatment with benralizumab in patients with severe eosinophilic asthma, paying particular attention to the impact on their quality of life (QoL).Materials and methods: In this prospective study, 10 outpatients with severe eosinophilic asthma were added-on with benralizumab and followed-up in our severe asthma clinic after 12 and 24 weeks. At each patient visit, pre-bronchodilator FEV1 and inflammatory markers were recorded. Variations in asthma symptoms control and QoL perception was assessed by validated questionnaires.Results: All the subjects experienced a marked reduction of nocturnal and diurnal symptoms over time and were able to stop using OCS, as documented by the improvement in Asthma control test (ACT) and Asthma Control Questionnaire score. Similarly, we recorded a statistically significant increase in patient's QoL perception in EQ-VAS, EQ-5D-3L and Asthma Quality of Life Questionnaire (AQLQ) assessment (p < 0.05). Simultaneously we recorded a significant reduction in eosinophilic inflammation, an improvement in pre-bronchodilator FEV1. These results appear to be in line with those already obtained in the previous randomized controlled trials (RCTs).Conclusion: Our 24-weeks real life experience supports the effectiveness of an add-on treatment with benralizumab in reducing eosinophilic inflammation and OCS-use, increasing lung function and improving control of nocturnal and diurnal symptoms, as well as restoring severe asthma patients to a better QoL.